Extent of knowledge and application of the basics of biomechanics among Paralympic Games coaches - Alkhawaldeh, I.; Alzughialat, M. (International Journal of Disabilities Sports and Health Sciences, 2023)
This study aimed to identify the extent to which the bio-mechanical principles of human movement are known and applied in training the skill aspects of Paralympic coaches where the sample of the study consisted of 35 Paralympic coaches from several countries, all of whom are males. The average age of 42 ± 3.4 years. Their average training age was 7.5 ± 2.6 years. In order to achieve the study's objectives, the researchers designed a cognitive test that its validity, reliability, difficulty index were confirmed, and composed of 51 questions distributed to 6 axes. They also designed a questionnaire that its validity and reliability were confirmed and consistent and made up of (38) A paragraph distributed to (6) axes. The study results showed a low level of knowledge and low degree of application of the basics of biomechanics among Paralympic coaches. According to the results of our study, The responsible authorities of the Paralympic Committees should provide their coaches with special courses in biomechanical analysis and enhance their capabilities in this field, given its practical importance.. Academic agencies that issue training certificates in the field of sports training for persons with disabilities should focus on the field of biomechanical analysis and its related matters in their teaching programs.